Carbon-nanotube/sulfur cathode with in-situ assembled Si3N4/graphene interlayer for high-rate and long cycling-life lithium-sulfur batteries. (10th February 2019) - Qu, Long; Liu, Pei; Zhang, Peng; Wang, Tao; Yi, Yikun; Yang, Pu; Tian, Xiaolu; Li, Mingtao; Yang, Bolun
Abstract: A Si3 N4 /graphene composite is designed as an interlayer for a carbon-nanotubes/sulfur cathode to improve electrochemical performance of lithium-sulfur batteries. In the interlayer, Si3 N4 nanoparticles suppress the migration of the dissolved polysulfides and graphene sheets construct a 3-dimensional charge-transfer network. The carbon-nanotubes/sulfur@Si3 N4 /graphene cathode delivers an initial discharge capacity of 1334.7 mAh g −1 at 0.1 C and retains a capacity as high as 745.8 mAh g −1 after 200 cycles, with a capacity fade ratio of 0.22% per cycle. The cathode shows good cycling life, delivering a discharge capacity of 413.3 mAh g −1 for 1 C after 1000 cycles. According to the results of density functional theory calculation, the anchoring of the Si3 N4 /graphene interlayer to lithium polysulfide can be attributed to a coefficient chemical binding of Li-N and Si-S bonds generating from electronic conjugation effect between the Si3 N4 supercell surface and the polysulfides. Generally, the improvement in electrochemical performance originates from the enhancements in Li + diffusion coefficient and charge transfer, and from the restraining of the shuttle effect of the dissolved lithium polysulfide as a result of the Si3 N4 /graphene interlayer. Graphical abstract: Image 1 Highlights: Si3 N4 /graphene interlayer anchors polysulfide via physical and chemical interactions. Si3 N4 /graphene interlayer constructs a 3D network of charge transfer. CNTs/S@Si3 N4 /graphene cathode exhibits ultralong cycling life.